Answer:
Step-by-step explanation:
<u>The quotient of </u>
- 5/6÷ (-13/7) =
- 5/6×(-7/13) =
- - 35/78
Answer:
hope it is correct
Step-by-step explanation:
i think it is more than, can , cannot, and required
Answer:
2(x + y)² - 9( x + y ) -5 = 0
⇒2(x + y)² - 10 (x+y) +1(x+y) -5 = 0
⇒2(x+y)(x + y - 5 ) + 1(x + y -5 ) = 0
taking (x + y -5 ) common ,
⇒(x + y -5 )[2(x + y) + 1] =0
⇒(x + y -5)(2x + 2y +1) =0
hope , you got this
Answer:
Step-by-step explanation:
The answere is no solution, there are no values of X that makes the inequality true, therefore there is no solution
Answer: 14.5 in, 14.8in, 15 in, 15.3 in, 15.8 in,